An Adlerian Reading of Courage, Life Style and Social Interest in Donoghue’s Room - Mehrnaz Khoshgam; Fatemeh Kargar Bardaskan; Seyed Hadi Momen (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
This paper aims to investigate the notion of Courage, Life Style and Social Interest in dealt with Adler concept of personality development in Emma Donoghue’s Room. Specifically, how these concepts unveil negative emotions encouraged the characters to develop their personality through the novel and how the characters resolve the personality problems in this novel. The protagonist, Jack, is a five-year-old youngster. room is in a whole different circumstance than she has ever been in. Jack grows up alone in a room with his mother. Since she was 19 years old, Ma has been kidnapped. It has been seven years since that time. She is raped and imprisoned in a room until her son, Jack, was born. Life in room, as Jack refers to their zone of imprisonment, is a constant pain for Ma, only alleviated by her desire to protect her son. In their daily lives in Room, they experience horrific events that can be classified as psychological illnesses for Ma and Jack . The focus of this study is on Adler’s most influential concept that is personality development. It is considered as an individual’s interest within their social context.